2009
DOI: 10.1182/blood-2009-03-213561
|View full text |Cite
|
Sign up to set email alerts
|

Microchimerism is strongly correlated with tolerance to noninherited maternal antigens in mice

Abstract: In mice and humans, the immunologic effects of developmental exposure to noninherited maternal antigens (NIMAs) are quite variable. This heterogeneity likely reflects differences in the relative levels of NIMA-specific T regulatory (T R ) versus T effector (T E ) cells. We hypothesized that maintenance of NIMA-specific T R cells in the adult requires continuous exposure to maternal cells and antigens (eg, maternal microchimerism [MMc]). To test this idea, we used 2 sensitive quantitative polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
144
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(153 citation statements)
references
References 54 publications
8
144
1
Order By: Relevance
“…4C). These results suggest that the level of MMc was correlated with tolerogenic effect of the NIMA, supporting the recent report (30).…”
Section: Correlation Between MMC and The Tolerogenic Nima Effectsupporting
confidence: 91%
See 1 more Smart Citation
“…4C). These results suggest that the level of MMc was correlated with tolerogenic effect of the NIMA, supporting the recent report (30).…”
Section: Correlation Between MMC and The Tolerogenic Nima Effectsupporting
confidence: 91%
“…The factors that govern MMc are poorly understood, but may be of considerable clinical relevance in view of the fact that MMc has been associated with autoimmunity and allograft tolerance (30). We analyzed the levels of MMc in young adults of NIMA-exposed mice using nested PCR for MHC class II Eb d -specific DNA.…”
Section: Correlation Between MMC and The Tolerogenic Nima Effectmentioning
confidence: 99%
“…These cells impart durable tolerance to non-inherited maternal antigens, an effect which can impact maternal health and transplant outcomes later in life. 34,35 We previously found that in normal pregnancy, cells from a woman's own mother (MP) are detectable in circulation, particularly during the third trimester. In the same study, MP microchimerism was not detected in preeclampsia, a pregnancy disorder thought by some to reflect maternal immune dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…42 Similar observations were recently made in a murine F1 breeding model, in which detectable levels of maternal CD11b ϩ monocytes or CD11c expressing mDC correlated with the presence of a dominant population of transforming growth factor ␤-producing CD4 ϩ T REG in NIMA tolerant offspring. 43 From 8 donors (6 females and 2 males), sufficient numbers of PBMCs were available to determine the copresence of microchimeric cells expressing the relevant minor H alloantigen. Using DNA extracted from highly purified hematopoietic cell fractions and real-time PCR technology, we were able to demonstrate the presence of minimally one microchimeric cell type in 7 of 8 donors tested (data not shown).…”
Section: Discussionmentioning
confidence: 99%